Frequency of iron deficiency anaemia in chronic kidney disease patients not on dialysis - Kamil, Faryal; Dhrolia, Murtaza; Hamid, Aamna; Qureshi, Ruqaya; Nasir, Kiran; Ahmad, Aasim (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of iron deficiency anaemia in non-dialysis chronic kidney disease patients. Method: The observational, cross-sectional study was conducted at the Department of Nephrology, The Kidney Centre Post-Graduate Training Institute, Karachi, from April 27 to October 26, 2018, and comprised adult patients of either gender diagnosed with anaemia and estimated glomerular filtration rate <90ml/min. Patient with transferrin saturation <20% were labelled as having iron deficiency anaemia. Data was analysed using SPSS 21. Results: Of the 366 participants, 185(50.5%) were males and 181(49.5%) were females. The overall mean age was 54.47±14.93 years. The most prevalent comorbid was hypertension 263(71.9%), followed by diabetes mellitus 187(51.1%) and cardiovascular disease 54(14.8%). Besides, 192(52.5%) patients had CKD stage 5 followed by 115(31.4%) and 54(14.8%) with CKD stages 4 and 3, respectively. The mean haemoglobin was 9.17±1.57g/dL. Iron deficiency was found in 285(77.9%) patients. Conclusion: Iron deficiency anaemia was found to be highly prevalent and should be screened routinely and managed appropriately. Key Words: Iron deficiency, Anaemia, Chronic kidney disease.